The military activity of founder of the 18th Egyptian dynasty the king "Ahmos I" (1550- 1525 BC) - Sakour, Baraa; Aboud, Dalia (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
This research deals with one side of the Egyptian king during the eighteenth dynasty time (1550- 1295BC), namely the military activity of the king "Ahmos I" (1550- 1525 BC) founder of the eighteen dynasty, identifying names and titles of the king "AhmosI" how he received the throne and his foundation the 18th dynasty, then the research moves to explain the military activity of this king on two axes, the first axis liberation the country and defense of it through his wars against Hyksos and expulsion them from Egypt, the second axis is about expanding his power through dominating of Nubia. All of this is based on the information contained in the Egyptian inscriptions, especially inscriptions of the tomb of "Ahmos son of Ibban" one of the king "Ahoms,s I" leaders and which explain the activity of this king from a military point of view, finally there are the most important results which the research concluded.